Georgia Architectural and Historic Properties Survey of Rural [241] Southern section of the county, Valdosta, Ga. December 1980. - Smith and Bartholomew (South Georgia Area Planning and Development Commission, 1980)
Georgia Architectural and Historic Properties Survey of Rural [241] Southern section of the county, Valdosta, Ga. December 1980. A one story rectangular plan with gabled roof and clapboard siding. Gabled porch, large sash windows with 9/9 lights. Brick piers. Double doors. Good condition. Date of Construction: c. 1910. A typical rural church common to this area.
Georgia Architectural and Historic Properties Survey of Rural [241] Southern section of the county, Valdosta, Ga. December 1980. 1 electronic record and assets. Digitized from originals. 1 PDF. 3 scans. photograph. 2400 DPI TIF. 300 DPI 4x6 JPG. 1.20 MB (1,268,429 bytes).
Keywords: Historic buildings; Real property surveys; Brooks County (Ga.); Lowndes County Historical Society (Lowndes County, Ga.); Valdosta (Ga.)